Navigating the indicator jungle: A roadmap to analyze common agricultural policy indicators - Anne-Katrin Gorn; Ayoub Barissoul; Christine Wieck (Universität Hohenheim, Institut für Agrarpolitik und Landwirtschaftliche Marktlehre, 2024)
The CAP monitoring framework includes a wide range of policy indicators, covering output, results, context, and impact. In environmental policy sciences, the complexities of analysing policy instruments and indicators are well known and techniques like statistical pattern analysis and grouping indicators into "umbrella" or composite indicators are recommended to simplify analysis. These methods are less common in agricultural economics and political sciences. This working paper investigates methods for constructing umbrella indicators and presents a literature-based roadmap for their application to the CAP indicators. It demonstrates that these methods can be successfully applied not only in other scientific fields but also to CAP indicators. – – Der GAP-Überwachungsrahmen umfasst eine breite Palette von Politikindikatoren, die Output, Ergebnisse, Kontext und Auswirkungen abdecken. In den Umweltpolitikwissenschaft ist die Komplexität der Analyse von politischen Instrumenten und Indikatoren bekannt, und Techniken wie die statistische Musteranalyse und die Gruppierung von Indikatoren zu 'übergeordneten" oder zusammengesetzten Indikatoren werden zur Vereinfachung der Analyse empfohlen. Diese Methoden sind in der Agrarwirtschaft und den Politikwissenschaften weniger verbreitet. In diesem Arbeitspapier werden Methoden zur Konstruktion von Dachindikatoren untersucht und ein literaturgestützter Fahrplan für ihre Anwendung auf die GAP-Indikatoren vorgestellt. Es wird gezeigt, dass diese Methoden nicht nur in anderen wissenschaftlichen Bereichen, sondern auch auf die GAP-Indikatoren erfolgreich angewendet werden können.
Keywords: 330; CAP; Monitoring Framework; Umbrella Indicator; Policy Outcomes